Skilled Nursing Facility Participation in Bundled Payments Was Related to Small Increases in Nurse Staffing Levels. (March 2023) - Ying, Meiling; Temkin-Greener, Helena; Thirukumaran, Caroline P.; Joynt Maddox, Karen E.; Holloway, Robert G.; Li, Yue
Medicare implemented Bundled Payments for Care Improvement (BPCI) Model 3 in 2013, in which participating skilled nursing facilities (SNFs) were accountable for episode costs. We performed comparative interrupted time series analyses to evaluate associations between SNF BPCI participation and nurse staffing levels, using Medicare claims, resident assessments, and facility-level and market-level files of 2010–2017. For persistent-participating SNFs, BPCI was associated with improved certified nursing assistant (CNA) staffing levels (differential change = .03 hours, p = .025). However, BPCI was not related to changes in registered nurse (RN) and all licensed nurse hours, and nurse skill mix. Among drop-out SNFs, BPCI was associated with increased RN staffing levels (differential change = .02 hours, p = .009), leading to a higher nurse skill ratio (0.51 percentage points, p = .016) than control SNFs. Bundled payments for care improvement had no impact on CNA and all licensed nurse staffing levels. In conclusion, BPCI was associated with statistically significant but small increases in nurse staffing levels.